Immunosuppressant Medication Use in Patients with Kidney Allograft Failure: A Prospective Multicenter Canadian Cohort Study. Issue 6 (June 2022) - Knoll, Greg; Campbell, Patricia; Chassé, Michaël; Fergusson, Dean; Ramsay, Tim; Karnabi, Priscilla; Perl, Jeffrey; House, Andrew A.; Kim, Joseph; Johnston, Olwyn; Mainra, Rahul; Houde, Isabelle; et al.
Significance Statement: Current recommendations suggest discontinuation of immunosuppressants 1 year after kidney transplant failure. In this first prospective multicenter study of 269 patients with kidney transplant failure in 16 Canadian centers, most patients were prescribed immunosuppressants for longer than 2 years. Continued use of immunosuppressants was not associated with an increased risk of death or hospitalized infection. However, the continued use of immunosuppressants did not prevent rejection of the failed allograft or an increase in anti-HLA antibodies, possibly due to inadequate drug exposure. The findings challenge current recommendations and highlight the need for a controlled trial of immunosuppressant use in patients with transplant failure. Abstract : Background: Patients with kidney transplant failure have a high risk of hospitalization and death due to infection. The optimal use of immunosuppressants after transplant failure remains uncertain and clinical practice varies widely. Methods: This prospective cohort study enrolled patients within 21 days of starting dialysis after transplant failure in 16 Canadian centers. Immunosuppressant medication use, death, hospitalized infection, rejection of the failed allograft, and anti-HLA panel reactive antibodies were determined at 1, 3, 6, and 12 months and and then twice yearly until death, repeat transplantation, or loss to follow-up. Results: The 269 study patients were followed for a median of 558 days. There were 33 deaths, 143 patients hospitalized for infection, and 21 rejections. Most patients (65%) continued immunosuppressants, 20% continued prednisone only, and 15% discontinued all immunosuppressants. In multivariable models, patients who continued immunosuppressants had a lower risk of death (hazard ratio [HR], 0.40; 95% confidence interval [CI], 0.17 to 0.93) and were not at increased risk of hospitalized infection (HR, 1.81; 95% CI, 0.82 to 4.0) compared with patients who discontinued all immunosuppressants or continued prednisone only. The mean class I and class II panel reactive antibodies increased from 11% to 27% and from 25% to 47%, respectively, but did not differ by immunosuppressant use. Continuation of immunosuppressants was not protective of rejection of the failed allograft (HR, 0.81; 95% CI, 0.22 to 2.94). Conclusions: Prolonged use of immunosuppressants >1 year after transplant failure was not associated with a higher risk of death or hospitalized infection but was insufficient to prevent higher anti-HLA antibodies or rejection of the failed allograft.